100 reglas de Brasilia: Propuestas para asegurar el derecho de acceso a la justicia de las personas en condiciones de pobreza - Salazar Soplapuco, Jorge Luis (2022)
Access to justice is a fundamental right in any democratic society and is an essential feature ofa Constitutional State. This right is contemplated in various international human rights legal instruments and in most constitutions of the American States and the world. However, its exercise is hindered by different social, economic, cultural and political circumstances that people suffer, the same ones that constitute conditions of vulnerability.Likewise, this right is affected or restricted by State omissions in relation to the elaboration of public policies that entail the eradication of these obstacles to its exercise. Precisely, the 100 Rules of Brasilia adopted by the representatives of the judiciary, ombudsmen's offices and other institutions of the American countries, seek to agree on governmental initiatives so that States promote and enable populations in vulnerable situations to exercise their right of access to justice. Finally, this article considers several proposals so that, taking into account the 100 Rules of Brasilia, the Peruvian State promotes and facilitates access to justice for people immersed in degrees of poverty and vulnerability.